PROFIL SISWA MEMAHAMI KONSEP BARISAN DAN DERET BERDASARKAN TAHAP BELAJAR DIENES DI KELAS IX-C SMP NURIS JEMBER - Nurfadilah, Nurfadilah; Suharto, Suharto; Setiawani, Susi (Department of Mathematics Education , University of Jember, 2016)
Abstract. This study aims to describe the students understanding in concept of sequence and series based on the Dienes learning stage in class IX-C SMP Nuris Jember. Type of this research is descriptive research with qualitative approach. The subjects in this study were 35 students of class IX-C who have completed the question oftest understanding, then selected 8 students as representatives of each category to be interviewed that is 2 students with an understanding of the concept of high, 3 students with an understanding of the concept of medium, and 3 students with an understanding of the concept of low. Data analysis based on test and interview. Students with an understanding of the concept of high tend to fulfill all stages on arithmetic and geometry sequence. But on the arithmetic and geometry series tend to fulfill 5 stages. Students with an understanding of the concept of medium tend to fulfill 4 stages and only 1 indicator for fifth stage. Students with an understanding of the concept of low tend to fulfill 4 stages in sequence and series arithmetic, and fulfill 2 stages of the sequence and series geometry. Keywords : Sequence and Series, Understanding The Concept, Dienes Learning Stage.